Metal organic vapor phase epitaxy of P-on-n HgCdTe/GaAs heterojunction - Song, JH; Kim, JS; Jung, KU; Suh, SH; Kim, SU; Park, MJ (INFRARED TECHNOLOGY AND APPLICATIONS XXIV, PTS 1-2, 1998)
We report in-situ growth of MWIR P-on-n HgCdTe on GaAs by Metal Organic Vapor Phase Epitaxy. HgCdTe epi layers were grown by interdiffused multilayer process(IMP). Tris-dimethylarminoarsenic (DMAAs) was used as a precursor for arsenic doping (p-type layer) and isoprophyliodide (IPI) was used for iodine doping (n-type layer). Standard bubbler configuration was used for both precursors. Doping concentration could be controlled accurately in the range of 2x10(15) to 7x10(16) cm(-3). After growth, HgCdTe layers were annealed in Hg-atmosphere at 415 degrees C and 260 degrees C consecutively. This Hg-annealing is for activating dopants and then reducing Hg-vacancy concentration. The layers doped with iodine in low 10(15) cm(-3) concentration showed higher Hall mobility than undoped layers. The Hall mobility of iodine doped layers decreased with increasing doping concentration. Secondary ion mass spectroscopy (SIMS) analyses for the iodine-doped layer showed sharp decrease of iodine concentration after IPI precursor being turned off, indicating negligible memory effect and very slow diffusion of iodine during growth and Hg-annealing. SIMS analyses for the arsenic doped layer showed that arsenic diffused by about 1 mu m during growth and Hg-annealing. These results show that IPI and DMAAs could be used as stable precursors for in-situ growth of HgCdTe heterojunction. A P-on-n structure was grown. The P-layer has x composition of 0.32 and acceptor concentration of 6x10(16) cm(-3). The n-layer has x composition of 0.30 and donor concentration of 2x10(15) cm(-3). SIMS depth profile for the structure shows well-defined regions of doping concentration and alloy composition. After Hg-annealed, P-on-n structures were fabricated into MESA structure diodes. Electron beam evaporated CdZnTe was used as a passivation layer This MWIR diode had R(0)A value of about 3x10(4) Omega.cm(2).